Francis Bacon’s Concept of Science and Scientific Method - Seyed Mohammad Reza Hosseini Beheshti (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
By the new foundation of philosophy and science, the concept of method gains the main status among many scholars of the new ages. The “forerunners” of philosophy and science sought the way out of the skepticism, that emerged from the endless controversies concerning the universals and the possibility of rational and philosophical knowledge about nature during the High and Late scholasticism, in the concept of “method”. As one of these founders, Francis Bacon has tried to define and describe his conception of the method. He makes use of the metaphors of ship, labyrinth, thread, and trial-court to put light on his account of scientific research. These metaphors, enable us to reconstruct the various features of his account of method and his expectations of applying method in the realm of natural sciences.